2020
DOI: 10.1038/s41598-020-66449-0
|View full text |Cite
|
Sign up to set email alerts
|

The tumor immune microenvironmental analysis of 2,033 transcriptomes across 7 cancer types

Abstract: Understanding the tumor microenvironment is important to efficiently identify appropriate patients for immunotherapies in a variety of cancers. Here, we presented the tumor microenvironmental analysis of 2,033 cancer samples across 7 cancer types: colon adenocarcinoma, skin cutaneous melanoma, kidney renal papillary cell carcinoma, sarcoma, pancreatic adenocarcinoma, glioblastoma multiforme, and pheochromocytoma / paraganglioma from The Cancer Genome Atlas cohort. Unsupervised hierarchical clustering based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…The correlation between immune and stromal scores along with the TMB values among four TSG subgroups indicated that the stromal and immune cells were strongly correlated with the mutational burden regardless of subtype, which was consistent with previous results that the tumor cells with high TMB and the formation of neoantigens had a decisive effect on the defective immune system and TME including tumor immunogenicity ( 22 , 34 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation between immune and stromal scores along with the TMB values among four TSG subgroups indicated that the stromal and immune cells were strongly correlated with the mutational burden regardless of subtype, which was consistent with previous results that the tumor cells with high TMB and the formation of neoantigens had a decisive effect on the defective immune system and TME including tumor immunogenicity ( 22 , 34 ).…”
Section: Discussionsupporting
confidence: 91%
“…The data preprocessing was performed by the previously reported pipeline ( 20 22 ). The number of raw reads (HTSeq count for Ensembl annotated gene) was transformed to variance transformed data (R package ‘DESeq2’) for transcriptomic sequencing analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The tumor microenvironment (TME), defined as the tissue environment surrounding a tumor, plays an important role in the tumorigenesis and prognosis of colon cancer. The TME contains not only cancer cells but also noncancer cells, including components of the extracellular matrix, blood vessels, immune cells, neurons, and cells that perform other tissue functions; these cell types all contribute to the malignant phenotypes of cancer, including uncontrolled proliferation, resistance to apoptosis, and evasion of immune surveillance [ 5 , 6 ]. Thus, the composition and proportion of stromal and immune cells in the TME may significantly influence therapeutic responses and clinical outcomes in cancer patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…An accurate pathological stage is an important basis for selecting lung cancer treatment. Nevertheless, the complexity and heterogeneity of tumor immunosuppressive microenvironment led to discrepant immunotherapy effects among patients at the same pathologic stages [ 9 ]. For particular individuals, the survival benefits of immunotherapy are minimal and with side effects.…”
Section: Introductionmentioning
confidence: 99%